The Effect of Brand Evaluation and Brand Relationship on Brand Loyalty of MG Coffee and Resto in Pringsewu - Muhammad Millenio Rizky Ramadhan; Satria Bangsawan; Dwi Asri Siti Ambarwati (Inovbook Publications, 2023)
This study aims to examine the effect of brand evaluation and brand relations on brand loyalty of MG Coffee and Resto in Pringsewu. The object of this research is MG Coffee and Resto in Pringsewu. The type of data used in this research is quantitative data. Methods of data collection by literature study and questionnaires with data testing techniques based on descriptive statistical analysis, validity test, reliability test, multiple linear regression analysis, hypothesis testing. From the results of the analysis of this study it is known that brand evaluation has a significant positive effect on brand loyalty as evidenced by the t test value on brand evaluation of 8,846. Brand relations have a significant positive effect on brand loyalty as evidenced by the t test value on brand relations of 21,630.